SEMASIOLOGY IN LEXICOGRAPHY: PRINCIPLES OF MEANING REPRESENTATION IN DICTIONARIES - Choriyev Botir; Mardonova Sevinch (TADQIQOTLAR, 2026)
Abstract: This article explores the role of semasiology — the study of word meaning — in the theory and practice of lexicography. While lexicography traditionally focuses on the collection, definition, and arrangement of lexical units, semasiology provides the conceptual framework for understanding how meanings are structured, distinguished, and related within a dictionary entry. The article discusses key semasiological phenomena such as polysemy, homonymy, synonymy, and semantic change, and demonstrates how each affects the lexicographer’s decisions. Special attention is given to the treatment of polysemous words, the ordering of senses, and the use of definitions, examples, and labels. The article argues that a systematic semasiological approach significantly improves dictionary quality and user orientation.